Effect on Rapid Thermal Oxidation process on Electrical Properties of Porous Silicon - Khawla S. Khashan; Amany A. Awaad; Maysaa A.Mohamed (Engineering and Technology Journal, 2009)
In this work, the porous silicon was prepared by using stain etching in HF-HNO3 atdifferent etching times. Then Rapid Thermal Oxidation (RTO) processes were used forsurface treatment at different temperature and oxidation time to enhancement sampleproperties. Fourier Transforms infrared (FTIR) spectrum exhibit the formation of SiHx(x=1, 2) and Si-O bonds which indicate the present of porous structure and formation ofoxidation porous layer. The Capacitance – Voltage characteristics reveal that effectivecarrier density is 36*1015 cm-3 for sample etching time at 2min, while there was achange from (37.8*1015 to 45.7*1015) cm-3 for sample oxidation at different oxidationtemperature (373 – 973)K and from (38.2*1015 to 40*1015) cm-3 for sample oxidation atdifferent oxidation time (0.5 – 3.5)min. Also the porosity was (45.56%) for PS/p-Sietching at 2min while reduce from (45% to 35.4%) with oxidation temperature, and from(44.2% to 40.5%) with oxidation time. From photocurrent characterized, that thephotosensitivity for PS/p-Si structure is better where etching time at 2min, and its 0.2545A/W at 370nm, and it increased after Rapid Thermal Oxidation (RTO) from (0.34 to0.44) A/W with different oxidation temperature, and changed from (0.35 to 0.34) A/Wwith different oxidation time, so that sandwich hetrojunction exhibit good efficiencyphotodiode.